ACEH TRADITIONAL HOUSE: ADVANTAGE OF THE BUILDING DESIGN IN RESPONDING TO THE TROPICAL CLIMATE - Annisa, Astrid; Nasution, Mufti Ali (Arsitekno, 2025)
Tropical architecture is a building design concept that adapts to the tropical climate, which must be able to overcome climate problems. Aceh traditional house commonly called ˜Rumoh Aceh, is the traditional house that is still inhabited by the Acehnese community nowadays. The building design of Aceh traditional houses is proven to have many advantages compared to modern houses nowadays, in terms of structure, construction, and also thermal comfort. The purpose of this paper is to investigate the tropical wisdom in Aceh traditional houses by learning the implementation of the design, to know how it provides comfort for the users. Qualitative research is a method used to identify the effectiveness of the building design strategy of the houses in adapting to tropical climates. The data collection is done through observation, interview, and documentation. The result shows that the Aceh traditional house apply tropical wisdom in its building design. The wisdom of tropical design elements in the houses is seen from the north-south orientation of building mass, the use of stage-form in the building to optimize air circulation, the appropriate placement of air ventilation, the open space for the interior concept, the use of environmentally friendly local material, and the use of sloping roof with a wide overhang to quickly channel rainwater, prevent rain splashes, and prevent strong winds from damaging the roof structure.